Iron oxide rock artefacts in Mesopotamia c. 2600-1200 BC : an interdisciplinary study of hematite, goethite and magnetite objects - Melein, Martine Marieke, (Archaeopress Publishing Ltd, 2018)
The flourishing civilisations of Mesopotamia imported all kinds of materials from the surrounding regions. Iron oxide rock was very popular for weight stones and cylinder seals around 2000 BC. This research aims to determine the region of origin for the raw material, what made people start using iron oxide rock, and what led them to stop using it.